Coral geochemical signals and growth responses to coseismic uplift during the great Sumatran megathrust earthquakes of 2004 and 2005. (15th March 2020) - Ito, Saori; Yamazaki, Atsuko; Nishimura, Yuichi; Yulianto, Eko; Watanabe, Tsuyoshi
Abstract: The annual banded skeletons of reef corals potentially record past earthquakes events. We examined cores of five living Porites coral heads in Simeulue Island, Indonesia, near the epicenter of the 2004 Sumatra-Andaman and the 2005 Nias-Simeulue earthquakes. These sites showed 0.4–1.4 m of uplift. We measured skeletal strontium, magnesium, and calcium; carbon and oxygen isotopic ratios; and skeletal density, extension, and calcification rates, from 1994 to 2010. Coral geochemistry fluctuates more than are expected from strictly environmental causes; however, stress bands, reduced growth rates, and changed skeletal δ 13 C appear to reflect the tsunami and seismic uplift (the step change in skeletal δ 13 C results equated to 0.31 ± 0.10‰/m in response to the 2004 uplift and 0.23 ± 0.03‰/m to the 2005 uplift).